co-organiser as convenor of the Populism Specialist Group that is one of the two groups that organise this event. - Venizelos, Giorgos (My University, 2026)
with leading scholars as keynote speakers: María Esperanza Casullo, Universidad Nacional de Río Negro Benjamin Moffitt, Monash University